Determination of the Chemical Compositions of Clay Deposits from Some Part of South West Nigeria for Industrial Applications - Inegbenebor, A.I.; Inegbenebor, A.O.; Mordi, R.C.; Kalada, N.; Falomo, A.; Sanyaolu, P. (International Journal of Applied Sciences and Biotechnology, 2016)
Clay is one of the major raw materials in ceramics, paint and paper industries. In this paper, a report is given on the chemical composition of clay deposits in Ilaro and Ikorodu, South West Nigeria and their suitability as raw materials in the above mentioned industries is suggested by comparison of their composition with industry standards. The clay samples were activated with H2SO4 and their moisture content was determined. The mineral content of the clays was determined using atomic absorption spectroscopy, which showed significant presence of Si, Al, Fe, and Ti. The morphology of the clays was studied using scanning electron microscope (SEM/EDX) in combination with X-ray analysis. The investigation revealed the agglomeration of the particles of quartz and rutile on the surface structure of the activated clays. The results obtained from their observed properties and chemical compositions indicate that these clays are suitable for use in the ceramics, paint and paper industries. This proposition is supported by reduction in moisture contents of the activated clay samples from both Ilaro and Ikorodu. Int J Appl Sci Biotechnol, Vol 4(1): 21-26